1982
DOI: 10.1002/hed.2890040304
|View full text |Cite
|
Sign up to set email alerts
|

Framework invasion by laryngeal carcinomas

Abstract: The accuracy of standard clinical and radiologic methods in detecting invasion of the laryngeal framework or the presence of a transglottic tumor was examined by comparing clinical and pathologic findings in a series of 50 randomly selected laryngectomies for squamous carcinoma. Forty-two of the patients had received radiation therapy as primary treatment. The presence of pain referred to the ear immediately before laryngectomy indicated invasion of the laryngeal framework or spread into the extralaryngeal sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 20 publications
2
1
0
Order By: Relevance
“…This is supported by several previous studies, showing a high incidence of nodal metastasis with cartilage invasion [5,8,25]. Our present study showed no influence of cartilage invasion on prognosis and periods free of disease.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is supported by several previous studies, showing a high incidence of nodal metastasis with cartilage invasion [5,8,25]. Our present study showed no influence of cartilage invasion on prognosis and periods free of disease.…”
Section: Discussionsupporting
confidence: 92%
“…The incidence of cartilage invasion has varied from 35 to 75% [16,25,30]. Our present study showed a similar incidence (44%) of hyaline cartilage invasion.…”
Section: Discussionsupporting
confidence: 82%
“…The tumor-initiated inflammatory process then activates osteoclasts to erode the newly formed bone within the cartilaginous framework. Osteoclasts accumulated at the surface of ossified cartilage and destroyed it ahead of the advancing edge of the tumor 27 (Fig. 2).…”
Section: Cartilaginous Barriers To Tumor Spreadmentioning
confidence: 98%